Effects of Microalgal Food Quantity on Several Productivity-Related Parameters of the Calanoid Copepod Bestiolina similis (Calanoida: Paracalanidae) - Camus, Thomas; Rolla, Lucrezia; Jiang, Jufeng; Zeng, Chaoshu (Frontiers in Marine Science, 2021)
The optimization of copepod feeding protocol is paramount to improve culture productivity and to maintain favorable water quality parameters overtime, as well as saving operational costs by preventing the production of unnecessary quantities of microalgae. The influence of microalgal feeding concentration on major parameters related to culture productivity of the calanoid copepod Bestiolina similis (Paracalanidae) was investigated in a series of laboratory experiments. B. similis was fed eight different concentrations (0, 150, 300, 600, 900, 1,200, 1,500 and 1,800 μgC l–1) of a mixed microalgal diet consisting of Tahitian strain of Isochrysis species, Pavalova 50 and Tetraselmis chuii at 1:1:1 carbon ratio. The results indicate that female daily and cumulative egg production over lifespan, egg hatching rate, naupliar and copepodite survival and development, adult female life expectancy, population growth and fecal pellet production rate (FPPR) were all significantly affected by microalgae feeding ration. Conversely, no significant influence could be established between microalgae food concentration and egg diameter or adult sex ratio. Feeding rations as low as 150 μgC l–1 led to lower egg hatching rates, survival and development, adult female life expectancy and population growth compared with the higher microalgae rations tested. Feeding concentration ≤ 900 μgC l–1 significantly limited female daily egg and fecal pellet production rate, as well as their cumulative egg production over lifespan, when compared to a level of 900 μgC l–1. Bestiolina similis fed with 1,200 μgC l–1 significantly improved female egg and fecal pellet production when compared to the lower treatments and was responsible for the highest female lifespan egg production and population growth observed among all treatments. Feeding rations as high as 1,500 μgC l–1 and 1,800 μgC l–1 did not lead to significant improvement in any of the parameters measured. This is likely due to a saturation effect at high food concentration which is known to decrease calanoid copepods feeding efficiency. Finally, B. similis FPPR, used as a proxy for ingestion, was found to saturate at a microalgae concentration of 783.4 μgC l–1 using a non-linear Michael-Menton (2 parameters), indicating that CVI female ingestion did not increase significantly above this concentration. Based on the above results it is recommended that B. similis cultures should be fed at a concentration of 1,200 μgC l–1, and not above, as rations > 1,200 μgC l–1 will not significantly improve any of the productivity-related parameters observed in this study. Feeding rations should never be below 783.40 μgC l–1 as this is the threshold level below which adult female ingestion rates become limiting.